PENGGUNAAN METODE DEMONSTRASI DALAM MENINGKATKAN KETERAMPILAN PENGURUSAN JENAZAH SISWA KELAS XI IPA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA AL-HIDAYAT KECAMATAN KELUANG KABUPATEN MUSI BANYUASIN - Kukuh Handayani; Muhammad Fauzi; Munirul Ihwan (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2023)
This study aims to improve the ability to organize the bodies of class XI IPA stu- dents in PAI subjects at SMA Al-Hidayat by using the demonstration method. This research is a classroom action research ( CAR). Data collection was carried out with observation sheets and practical tests conducted at the end of each cycle consisting of planning, implementation, observation, and reflection. The subject of this reseach is the students of class XI IPA at SMA Al-Hidayat, totaling 29 people. In the use of this demonstration learning method an increase in the skills of organizing students’ bodies per cycle. The first cycle the average score of students 52,24%. Cycle II students’ average score of 75,68%. Cycle III students average score of 90%. From the results of this study it can be recommended that the use of demonstration methods can be ap- plied by teachers in learning PAI in schools to improve the skills lof organizing bodies.